U.S. Smart Power in Southeast Asia During the Obama Administration: More Hard or Soft Power? - Siangyen, Chamaiporn (Thai Journal of East Asian Studies, 2018)
This article examines the U.S. smart power strategy employed in Southeast Asia by the Obama government. It argues that, even though under the leadership of Obama the United States claimed to pursue a new and softer approach to reengaging Southeast Asian states, the U.S. rebalancing strategy did not in fact differ much from that of the Bush administration. Evidence shows that, although the Obama administration professed to change to a smart power framework, considerably more resources were still allocated to hard power than soft power. Hence, the essence of American smart power, as conducted by President Obama, was predominantly an extension of the hard power policies of his predecessor.